2018
DOI: 10.21873/anticanres.12903
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of MMP-7 Promoter Polymorphisms to Taiwan Lung Cancer Susceptibility

Abstract: Background/Aim: Matrix metalloproteinase-7 (MMP-7) plays an important role in metastasis behavior of cancer cells, and overexpression of MMP-7 has been associated with poor prognosis in non-small cell lung cancer. However, the contribution of various genotypes of has not yet been investigated in lung cancer in Taiwan. Therefore, this study aimed to investigate the association of MMP-7 genotypes with lung cancer risk among the Taiwanese. Materials and Methods: In this hospital-based case-control study, genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…In literature, the A-181G genotypes of MMP7 have been examined for their association with various types of cancer, including oral, breast, esophageal, gastric, colorectal, gallbladder, bladder, cervical cancer, leukemia and renal cell carcinoma (28,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). The lack of association of MMP7 genotype with pterygium in the current study, together with those in bladder (34), renal cell (44), oral (35), colorectal (28), and lung (46) cancer in Taiwan supports the concept that MMP7 may influence Taiwanese susceptibility to these diseases via other mechanisms, such as regulation of translation or protein-protein interaction, and simply not through the regulation at the transcriptional level via polymorphic variations in the promoter region. Notably, while the AG genotype at MMP7 promoter A-181G was associated with an OR of 1.22 (95% CI=0.91-1.63, p=0.2235), the GG genotype had an OR of 2.84 (95% CI=1.64-7.48, p=0.0007) compared to those carrying the AA wild-type genotype among a very large Taiwan population with 1,232 patients with breast cancer and 1,232 non-cancer controls (32).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, the A-181G genotypes of MMP7 have been examined for their association with various types of cancer, including oral, breast, esophageal, gastric, colorectal, gallbladder, bladder, cervical cancer, leukemia and renal cell carcinoma (28,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). The lack of association of MMP7 genotype with pterygium in the current study, together with those in bladder (34), renal cell (44), oral (35), colorectal (28), and lung (46) cancer in Taiwan supports the concept that MMP7 may influence Taiwanese susceptibility to these diseases via other mechanisms, such as regulation of translation or protein-protein interaction, and simply not through the regulation at the transcriptional level via polymorphic variations in the promoter region. Notably, while the AG genotype at MMP7 promoter A-181G was associated with an OR of 1.22 (95% CI=0.91-1.63, p=0.2235), the GG genotype had an OR of 2.84 (95% CI=1.64-7.48, p=0.0007) compared to those carrying the AA wild-type genotype among a very large Taiwan population with 1,232 patients with breast cancer and 1,232 non-cancer controls (32).…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping processes. The genomic DNA was extracted from the peripheral blood leucocytes of each participant within 24 h after their donation, and stored at −80˚C until processed as per our previous studies (30)(31)(32). In this study, the genotypes at -1306 and -735 polymorphic sites in the MMP-2 promoter region were determined for all the subjects in both the control and oral cancer patient groups.…”
Section: Methodsmentioning
confidence: 99%
“…In our body, MMP-7 has been shown to be constitutively produced by the mammary and parotid glands, pancreas, liver, prostate and lung peribronchial glands (16). In the past years, accumulating evidence indicated that the functional polymorphisms of MMPs may contribute to inter-individual differences in susceptibility to several types of cancer (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Furthermore, the basal promoter activity was higher in promoter constructs harboring the combination of the two rare alleles of MMP-7 at A-181G (rs11568818) and C-153T (rs11568819) (27).…”
mentioning
confidence: 99%